Efektivitas Seminar Fiqih Ubudiyah Dalam Pembelajaran Praktis Wudhu Di SDN 4 Jember Jawa Timur - Faiz Rahmawati (Impact: Jurnal Pengabdian kepada Masyarakat, 2024)
The fiqih ubudiyah seminar is an educational strategy that aims to improve students' understanding of the practice of ablution. This study aims to evaluate the effectiveness of the fiqih ubudiyah seminar in improving the skills of SDN 4 Jember Jawa Timur students in the correct ablution procedure. The method used was Community Engagement Research (CRI) with a descriptive qualitative approach. Data was collected through observation, in-depth interviews, and document analysis. The results showed that the seminar successfully improved students' understanding of ablution from 20% before the seminar to 50% after the hands-on session. Success factors of the programme include the participatory approach and students' active involvement in the ablution practice. However, challenges such as lack of support from parents and limited school facilities still need to be overcome.